2017
DOI: 10.1038/s41598-017-00033-x
|View full text |Cite
|
Sign up to set email alerts
|

A Global Approach for Quantitative Super Resolution and Electron Microscopy on Cryo and Epoxy Sections Using Self-labeling Protein Tags

Abstract: Correlative light and electron microscopy (CLEM) is a powerful approach to investigate the molecular ultrastructure of labeled cell compartments. However, quantitative CLEM studies are rare, mainly due to small sample sizes and the sensitivity of fluorescent proteins to strong fixatives and contrasting reagents for EM. Here, we show that fusion of a self-labeling protein to insulin allows for the quantification of age-distinct insulin granule pools in pancreatic beta cells by a combination of super resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 71 publications
3
56
0
Order By: Relevance
“…Here, were the structural preservation and labeling intensity satisfactory (Figure S3A,B) and sometimes quite good, though specimen contrast was lower than with cocktail UA/GA/OsO4. Such GA‐free samples from cells grown on (gridded) sapphire discs avoid the problem of GA‐induced autofluorescence and could, therefore be useful for certain kinds of complementary fluorescence microscopy and EM analyses . Notably, the majority of antibodies so far tested with our cryo‐based pre‐embedding approach was compatible with FS‐cocktails containing up to 0.05% OsO4 (in total: 11 out of 16).…”
Section: Resultssupporting
confidence: 92%
“…Here, were the structural preservation and labeling intensity satisfactory (Figure S3A,B) and sometimes quite good, though specimen contrast was lower than with cocktail UA/GA/OsO4. Such GA‐free samples from cells grown on (gridded) sapphire discs avoid the problem of GA‐induced autofluorescence and could, therefore be useful for certain kinds of complementary fluorescence microscopy and EM analyses . Notably, the majority of antibodies so far tested with our cryo‐based pre‐embedding approach was compatible with FS‐cocktails containing up to 0.05% OsO4 (in total: 11 out of 16).…”
Section: Resultssupporting
confidence: 92%
“…CLEM revealed that the ultrastructure of those complex objects resembled the classical morphology of MGBs, with several spherical electron dense particles enclosed within a large vesicle . Corroborating these findings, CLEM of labelled SOFIA mouse β‐cells revealed that starting 3 days after their biogenesis, more SGs were found within MGBs …”
Section: Intracellular Insulin Sg Degradation Depends On Sg Agementioning
confidence: 60%
“…The specific characteristics of the SNAP system allow for the analysis of the labelled SGs using different approaches including live‐cell imaging, microscopy of fixed samples, fluorimetry or immuno‐isolation (Figure ). Recently, we developed a protocol for correlative light and electron microscopy (CLEM) enabling the evaluation of labelled and unlabelled SGs in the same sample . By now, we successfully targeted insulin SGs of insulinoma cell lines and mice with the SNAP‐tag .…”
Section: Insulin‐snap As a Reliable Granule Age Reportermentioning
confidence: 99%
See 2 more Smart Citations